Dakwah Kreatif 6.0 sebagai New Local Wisdom dalam Melestarikan Nilai-Nilai Islam pada Generasi Z - Aini, Noviana (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Generation Z, as digital natives, possess unique characteristics that demand a new approach to Islamic propagation. Creative 6.0 Dawah, which integrates cutting-edge digital technologies with Islamic values, emerges as a new local wisdom to reach and inspire this generation. This article explores the concept of Creative 6.0 Dawah as an effective strategy for preserving Islamic values among Generation Z. This research analyzes how digital technologies such as social media, virtual reality, and artificial intelligence can be integrated into Dawah to create engaging, interactive, and relevant content for Generation Z. Furthermore, the article explores how Creative 6.0 Dawah can become a new local wisdom that adapts to the culture and lifestyle of Generation Z while upholding the essence of Islamic teachings. This study utilizes a qualitative approach with a phenomenological perspective and existential analysis. The research findings indicate that Creative 6.0 Dawah holds significant great potential to become a new local wisdom in preserving Islamic values among Generation Z. This is evident through its ability to meet the basic and non-material needs of Generation Z. Creative 6.0 Dawah also provides Generation Z with a deeper understanding of finding meaning, identity, and purpose in life within the context of Islamic values. This is achieved by providing platforms that enable self-exploration, building an identity based on Islamic values, bridging generational gaps, fostering community and support, and offering guidance in defining life goals.